Mierzenie przemian strukturalnych w gospodarce - Parkoła, Andrzej (Wydział Prawa i Administracji UAM, 1978)
The article deals with selected methodological problems connected with measurement of changes of economic structure. The statement, that economy structures can be illustrated from its quantitative aspect by percentage confrontation of shares of economy's particular parts like sectors, divisions or branches, is the starting point of the study. In the first part of the article structure measures have been discussed, i.e. the magnitudes with the aid of which the above mentioned shares can be expressed. Production values, size of employment and value of capital resources 'belong to them. The analysis of these measures leads to the conclusion that — on account of imperfections characteristic for each of them — the illustrated structure can be treated as some approximation to the „real" structure. The second part of the article is devoted to presentation of measures enabling quantification of the structure changes intensity. Coefficients constructed on the base of statistical measures of dispersion and on the base of a cosine of the angle between structure vectors belong to them. The measures discussed in that part of the article enable an objectivised appraisal of the intensity of structural changes. At the same time these measures enable carrying on comparative research on economic structure formation both in time and spatial approaches. In the final part of the article the method of examination of convergence of economic structures of different countries has been presented, what is of importance among others for an appraisal of integration processes.
The Measurement of Structural Changes in the Economy